PENGEMBANGAN STRATEGI KOMUNIKASI BIMAS ISLAM KABUPATEN PONOROGO DALAM SOSIALISASI BIMWIN - Mohammad Luthfi (Program Studi Ilmu Komunikasi, 2020)
Abstract: This study aims to examine the communication strategy of the Bimas Islam of Ponorogo Regency in the socialization of Marriage Guidance (BIMWIN) to the community, especially the bride and groom. The location of the research was the Bimas Islam of Ponorogo Regency office and the KUA Sawoo office with the research subjects being the Kasi Bimas Islam, the Head of KUA Sawoo and BIMWIN participants. Collecting data through observation of BIMWIN's socialization activities and in-depth interviews with 3 informants as well as documentation of the implementation of BIMWIN's socialization. The results showed that the communication strategy in BIMWIN socialization carried out by the Bimas Islam of Ponorogo Regency through instructions to the KUA of the district, then KUA conveyed BIMWIN information to the community and persuaded the bride and groom to follow BIMWIN. The obstacle is that there are people who are less concerned about BIMWIN activities due to their low level of understanding of the importance of BIMWIN. This research gives a positive contribution in the study of communication science, especially in developing communication strategies in BIMWIN socialization. Keywords: Communication Strategy, Socialization, BIMWIN